2020
DOI: 10.1111/os.12630
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Methylprednisolone‐Induced Primary Cilia Formation Disorder and Autophagy in Osteoblasts

Abstract: Objective: To study the role of primary cilia formation disorder and osteoblasts autophagy in the pathogenesis of steroid-induced avascular necrosis of the femoral head (SANFH).Methods: Osteoblasts were isolated from rabbit bones and treated with 1 μM Methylprednisolone for 0, 12, 24, 48, and 72 h. The Beclin1, MAP1LC3, Atg-5, Atg-12, IFT20 and OFD1 mRNAs and proteins were detected by PCR and Western blotting, and their correlation was statistically analyzed. The lengths of osteoblast cilia were measured under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In addition, Zhao et al reported that the autophagy flux in the rabbit osteoblasts increased and the ciliary length decreased in a timedependent manner after methylprednisolone treatment, so they speculated methylprednisolone inhibited primary cilia formation and promoted autophagy, which could be the pathological basis of GC-ONFH. 31 PENG et al's study also showed that the level of autophagy marker proteins was also significantly increased during the process of rat osteoblasts apoptosis induced by dexamethasone, while autophagy inhibitor 3-MA attenuated dexamethasonemediated apoptosis. 32 Both cell and animal experiments in this study demonstrated that lithium, as an autophagy regulator and osteogenic activator, can inhibit the excessive autophagy of osteoblasts induced by GC, while retaining the osteogenic activity of osteoblasts, and achieve the purpose of treating GC-ONFH in rats.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, Zhao et al reported that the autophagy flux in the rabbit osteoblasts increased and the ciliary length decreased in a timedependent manner after methylprednisolone treatment, so they speculated methylprednisolone inhibited primary cilia formation and promoted autophagy, which could be the pathological basis of GC-ONFH. 31 PENG et al's study also showed that the level of autophagy marker proteins was also significantly increased during the process of rat osteoblasts apoptosis induced by dexamethasone, while autophagy inhibitor 3-MA attenuated dexamethasonemediated apoptosis. 32 Both cell and animal experiments in this study demonstrated that lithium, as an autophagy regulator and osteogenic activator, can inhibit the excessive autophagy of osteoblasts induced by GC, while retaining the osteogenic activity of osteoblasts, and achieve the purpose of treating GC-ONFH in rats.…”
Section: Discussionmentioning
confidence: 92%
“… 11 In addition, Zhao et al reported that the autophagy flux in the rabbit osteoblasts increased and the ciliary length decreased in a time‐dependent manner after methylprednisolone treatment, so they speculated methylprednisolone inhibited primary cilia formation and promoted autophagy, which could be the pathological basis of GC‐ONFH. 31 PENG et al. 's study also showed that the level of autophagy marker proteins was also significantly increased during the process of rat osteoblasts apoptosis induced by dexamethasone, while autophagy inhibitor 3‐MA attenuated dexamethasone‐mediated apoptosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…OBs isolation and culture. Isolation and culture of OBs were performed as described by Zhao et al (20). New Zealand rabbits were anesthetized by intravenous injection of pentobarbital sodium.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study demonstrated that the osteoclastic-related genes OPG and RANML were abnormally expressed in SONFH, and therefore, they are potential diagnostic markers [6] . However, other processes, including coagulopathy [7] , dysregulated apoptosis [8] , and disordered lipid metabolism [9] were also crucial for SONFH. In addition, inflammatory pathways such as the PDK1/AKT/mTOR signaling pathway and the PERK and Parkin pathways [10,11] are utilized for the function of dysregulated genes in these function pathways might act as potential biomarkers of SONFH.…”
Section: Introductionmentioning
confidence: 99%